Dimensionamentos de pavimentos flexíveis pelos métodos DNER e MeDiNa em subleitos rodoviários no estado do Paraná - Silva, Marcos Filipe Neves da (2025)
The main Brazilian transport system is the road modal, which represents most of the cargo transport matrix on federal, state and municipal highways, of which they are characterized as regular to very poor quality due to the lack of compatibility of pavement sizing in design and maintenance and rehabilitation of highways. About paving, technological control criteria are increasingly demanded, especially in the analysis of fatigue cracked areas on the pavement surface and in the results of wheel track sinking. In view of this scenario, the present study aims to design new pavements by the methods proposed by DNIT, and to evaluate and compare the design of flexible pavements of four soils in different regions of the State of Paraná, namely: Paranaguá, Curitiba, Cascavel and Londrina. Traffic studies were carried out based on PNCT data on the BR-277 and BR-369 highways, where the collections were carried out for characterization tests and resilience module tests. In the DNER method compared to the MeDiNA method according to the data conditions for the design, the results obtained through the evolution of the fatigue damage, revealed a progressive increase in the cracked area for the 10-year design period, resulting in values above 30% of degraded area, reaching 31.35% in the 30th month of pavement life and cracked area for soils classified as A-7-6 and 33.43% of cracked area for soils classified as A-2-6. For the values obtained of permanent deformation, in all cases designed, the results were below the limit established by the 13 mm method. The high values of cracked areas verified by the MeDiNa method are related to the prolonged exposure of the structure to the action of traffic. Regarding the thicknesses of the structures dimensioned by the methods were 42.5 cm for the soil of Paranaguá, 52.50 cm for the soil of Curitiba, 42.5 cm for the soil of Cascavel and 70.0 cm of thickness for the soil of Londrina, these variations are the result of the characteristics of the geological formations of the soils used in road subgrades, as well as the study of traffic in the region. The results of the RM assays were 103.12 MPa and 98.34 MPa for the soils of the Serra Geral, Cascavel and Londrina formation group, respectively, and MR= 209.18 MPa for red clays of the Guabirotuba formation. For the soil classified as sandy A-2-6 from Paranaguá, the RM = 120.13 MPa. In the new analysis of the structure designed to satisfy the condition of % of cracked area of the pavement, it was concluded that these pavement thicknesses designed by the DNER could be even lower if the simulations were carried out by varying the thicknesses of the layers until reaching the limit of cracked areas of 30% in 10 years. Thus, the mechanistic-empirical analysis as a prediction of the behavior of flexible pavements.